The Leadership of the Caregivers of Salafy Islamic Boarding Schools in Facing the Challenges of Education Modernization - Moh Muksit; Ja’far Shodiq; Salman Alfarisi (Universitas Nurul Jadid, 2024)
This study aims to analyze the leadership role of Salaf Islamic boarding school caregivers in facing the challenges of educational modernization, including the development of physical and digital infrastructure and the management of internal resistance. The research method used is a case study with a qualitative approach, involving in-depth interviews with patient caregivers, teachers, staff, and students. The results of the study show that the leadership of caregivers who adopt a hybrid model, combining traditional values with modern innovations, can improve the quality of education and the competitiveness of graduates. The use of e-learning platforms and library digitization enhance the access and quality of student learning, while the development of adequate physical infrastructure creates a conducive learning environment. Internal resistance can be minimized through a dialogical and inclusive approach, which creates consensus and acceptance of change. Continuous evaluation ensures the effectiveness of the modernization programs implemented. The implications of this study emphasize the importance of adaptive and inclusive leadership in the face of change, as well as the need for technology integration in pesantren education to maintain relevance and quality in the modern era. This research makes a significant contribution to leadership literature in the context of Islamic education and offers a model that can be adopted by other Islamic boarding schools.